2020
DOI: 10.1097/gox.0000000000003010
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Biochemical, and Biologic Properties of Fat Graft Processed via Different Methods

Abstract: Background: Clinical use of autologous fat for correction of soft-tissue defects in cosmetic and reconstructive procedures has grown in popularity. Graft processing is implicated as one of the variable factors affecting quality, viability, and subsequent graft survival. This study analyzed the in vitro physical and biologic characteristics of lipoaspirate processed using different techniques. Methods: Fresh lipoaspirates from patients with informed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…51 In fact, their study found that centrifugation resulted in higher fat tissue content, though this did not translate into improved lipolysis activity. 51 Translation of these in vitro findings to in vivo fat retention has yet to be comparatively evaluated. Ultimately, based on prevailing theories on fat grafting, the aim of fat processing is to maximize the concentration of injected viable adipocytes during lipoaugmentation and/or activate adipose-derived stem cells to remodel the adipose tissue.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…51 In fact, their study found that centrifugation resulted in higher fat tissue content, though this did not translate into improved lipolysis activity. 51 Translation of these in vitro findings to in vivo fat retention has yet to be comparatively evaluated. Ultimately, based on prevailing theories on fat grafting, the aim of fat processing is to maximize the concentration of injected viable adipocytes during lipoaugmentation and/or activate adipose-derived stem cells to remodel the adipose tissue.…”
Section: Discussionmentioning
confidence: 95%
“…Translation of this single study to VF lipoaugmentation is unclear but suggests that fat can survive such centrifugation, though reported speeds and durations varied. A comparative review of adipocyte viability in vitro using various processing techniques supports similar viability with centrifugation compared to decantation and commercial processing kits 51 . In fact, their study found that centrifugation resulted in higher fat tissue content, though this did not translate into improved lipolysis activity 51 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32,33 Firstly, the results we obtained allow us to confirm results from several previous studies, namely that simple decantation of the tissue leads to inferior results to all other techniques tested. 24,27,30,34,35 Indeed, in this technique, the liquid represents up to 30% of the volume, 17 which may explain the poor grafting efficiency of about 60% (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…The PureGraft technology is based on the filtration of adipose tissue through a particular membrane, an equally rapid procedure (15 min). In addition, grafts from PureGraft displayed larger particles (>1000 μm) and were able to operate a “dialysis” of the adipose tissue without resorting to other, more destructive methods such as centrifugation [ 95 ]. The main use of these technologies is in the field of fat grafting for breast volumes [ 96 ].…”
Section: Regenerative Treatment For Osteoarthritis Diseasementioning
confidence: 99%